ANALISIS PENGEMBANGAN PARIWISATA BAGI EKONOMI LOKAL: (Studi Kasus: Desa Wisata Kampoeng Lama, Kec. Pantai Labu Kab. Deli Serdang) - Salsabila, Putri Filza; Harahap, Astri Sri Rezeki; Maulida, Lisa; Pranata, Mohammad Harry; Wulandari, Sari (STIE Mahardhika, 2025)
The purpose of this study is to ascertain how sustainable tourist development affects the regional economy. case study: Deli Serdang Regency's Pantai Labu District's Kampoeng Lama Tourism Village. This research employs a descriptive approach and a qualitative methodology. Interviews and observations are the sources of primary data. On the other hand, secondary data draws information from a variety of sources, including books, journals, and articles about the subject of the study. The study's findings suggest that the growth of tourism in Kampoeng Lama Tourism Village benefits the local economy. The creation of new jobs, higher community income, and more investment that supports the improvement of local services and infrastructure are some of the primary effects. This development is driven by local community participation and government support, as well as strategies that focus on local potential, including traditional culinary, crafts, and agricultural-based educational activities. As a result, Kampoeng Lama Tourism Village has been nationally recognized as one of the 75 best tourist villages in Indonesia in 2023.